Evaluation of two-sex determining systems in papaya plants (Carica papaya) Pococí hybrid - Barrantes-Santamaría, Walter Vicente; Loría-Quirós, Carlos; Gómez-Alpízar, Luis (Agronomía Mesoamericana, 2019)
Introduction. Papaya growers prefer hermaphrodite plants for their fruit characteristics, but they must wait until the beginning of flowering to identify and select plants. Currently, it is possible to determine the sex of papaya plants in the seedling stage using molecular markers. Objective. The objective of this research was to compare the vegetative and productive growth of papaya plants Pococí hybrid, sexed by two systems: conventional (CS) and molecular (MS). Materials and methods. For the conventional sexing system the traditional method of farmers sowing was used, which consists of planting three seedlings and determine the sex by visual inspection, eliminate female plants and leave a hermaphrodite plant per sowing site. In the molecular sexing system, sex was determined in the seedbed based on the molecular markers, and then a hermaphrodite plant was established per planting site. The trial was conducted on the farm of a papaya producer located in the Rita de Guapiles, Limon province, Costa Rica, between March and October of 2010. Results. No significant differences were observed for plant height and stem diameter with both sexing systems, indicating that the period of initial competition to which the seedlings were subjected in the SC system did not affect vegetative development. For the productive variables, significant differences were found between both sexing systems. SM plants presented flowering and fruit set at an earlier age. The total production and fruit quality were similar between both treatments. Conclusion. The sex-determining procedure did not influence the growth, development, and yield of the plants under this study condition, which indicates the possibility of using SM plants for cultivation of the Pococí hybrid.